Interstitial glycerol concentration in human skeletal muscle and adipose tissue is close to the concentration in blood. - Samra, J; Ravell, C; Giles, S; Arner, P; Frayn, K (1996)
1. The suggestion that the interstitial glycerol concentration in both adipose tissue and skeletal muscle is around 3 mmol/I (Maggs DG, Jacob R, Rife F, et al. J Clin Invest 1995; 96: 370-7), rather than close to the blood concentration as previously supposed, was tested by independent methods. 2. Free glycerol was infused, as part of a triacylglycerol emulsion, into six normal subjects and the arteriovenous difference for glycerol across the forearm was measured. In addition the relative interstitial glycerol concentration in subcutaneous adipose tissue was assessed simultaneously in four of the subjects by microdialysis. 3. During glycerol infusion the arterialized glycerol concentration rose from 52 +/- 5 mumol/I to 250-300 mumol/I (P < 0.001) in a square wave fashion. The net arteriovenous difference for glycerol across the forearm changed from negative (output) to positive (uptake) (P < 0.01). In subcutaneous adipose tissue the interstitial glycerol concentration rose during glycerol infusion (P < 0.001). 4. These observations are most easily explained by the movement of glycerol from plasma to interstitial fluid down a concentration gradient. We conclude that the interstitial glycerol concentration in skeletal muscle and adipose tissue is closer to the arterial concentration than to 3 mmol/I.